Pseudocapacitive performance of phenothiazine functionalized graphene aerogel - Lee, Soon Poh; Ali, Gomaa A.M.; Assiri, Mohammed Ali; Kong, Kien Voon; Teo, Ellie Yi Lih; Chong, Kwok Feng (Elsevier B.V., 2023)
This study utilizes light adsorbing molecule, phenothiazine (PTZ) to reduce graphene oxide (GO) and functionalize into PTZ-rGO aerogel (PTZ-rGO). The UV excited PTZ reduces GO via electron transfer while PTZ is simultaneously oxidized and functionalized onto rGO to produce PTZ-rGO aerogel. The optimum incorporation of PTZ on rGO sheets renders good electrochemical active surface area of 495.71 m2 g−1 and enhances the diffusion behavior up to 41.92%. This pseudocapacitive effect and the excellent surface property provide promising charge storage results of 235.5 F g−1 at 0.5 A g−1. Furthermore, the stable charge-discharge cycles with 92% capacitance retention after 10,000 cycles render it an excellent electrode material for supercapacitor fabrication.